Expansive cements for the manufacture of the concrete protective bandages - Yakymechko Yaroslav; Voloshynets Vladyslav (Selected Scientific Papers: Journal of Civil Engineering, 2017)
One of the promising directions of the use of expansive cements is making the protective bandages for the maintenance of pipelines. Bandages expansive application of the compositions of the pipeline reinforce the damaged area and reduce stress due to compressive stress in the cylindrical area. Such requirements are best suited for expansive compositions obtained from portland cement and modified quicklime. The article presents the results of expansive cements based on quick lime in order to implement protective bandages pipelines.